Implementation Of Strengthening Numeration Literacy And Adaptation Of Technology - Pratikno, Heru; Kokok Dj Purwanto; Atsani Wulansari (Universitas Nahdlatul Ulama Surabaya, 2024)
It turns out that education held in elementary schools still experiences many obstacles. The obstacles in question include the lack of professional teachers, low student ability, limited infrastructure, and so on. This is the kind of thing that is still being experienced by SDN KI Hajar Dewantara 01. Therefore, the aim of this service is that the team wants to inform the school about the causes of students' low ability in numeracy literacy. Apart from that, the team wants to provide solutions to teachers to improve students' abilities, especially in terms of strengthening numeracy literacy. Not only that, another goal is that the team wants to increase teachers' knowledge in adapting technology for learning. This service includes solving cases so that the suitable method used to analyze data is descriptive qualitative. The research results show that it is not enough to rely solely on school teachers to increase the strengthening of numeracy literacy. For this reason, contribution, collaboration and consistency from various interested parties are needed. Thus, the success of education at the elementary level needs to be fought for better continuity of further education.